Cellulose Nanocrystals from lignocellulosic agro-waste: A comparative study on Conventional and Ultrasonic Assisted Preparation Methods. (2019) - Saha, S.; Ghosh, R.
Abstract: Cellulose nano crystals (CNC) are smart organic rod-shaped nano material which can be derived from one of the most abundant biopolymer obtained from agro-waste materials; cellulose via acid hydrolysis. In this work CNCs have been prepared from sugarcane bagasse via acid hydrolysis at elevated temperature using mechanical stirring and ultrasonication and their efficiencies have been compared depending on the crystallinity, size and stability.